Surgical treatment of gastrointestinal stromal tumors of the duodenum: a literature review - Popivanov, Georgi; Tabakov, Mihail; Mantese, George; Cirocchi, Roberto; Piccinini, Irene; D’Andrea, Vito; Covarelli, Piero; Boselli, Carlo; Barberini, Francesco; Tabola, Renata; Pietro, Ursi; Cavaliere, Davide (Translational Gastroenterology and Hepatology; Vol 3 (September 2018): Translational Gastroenterology and Hepatology, 2018)
Background: Gastrointestinal stromal tumors (GIST) are the most frequent mesenchymal tumours in the digestive tract. The duodenal GIST (dGIST) is the rarest subtype, representing only 4–5% of all GIST, but up to 21% of the resected ones. The diagnostic and therapeutic management of dGIST may be difficult due to the rarity of this tumor, its anatomical location, and the clinical behavior that often mimic a variety of conditions; moreover, there is lack of consent for their treatment. This study has evaluated the scientific literature to provide consensus on the diagnosis of dGIST and to outline possible options for surgical treatment. Methods: An extensive research has been carried out on the electronic databases MEDLINE, Scopus, EMBASE and Cochrane to identify all clinical trials that report an event or case series of dGIST. Results: Eighty-six studies that met the inclusion criteria were identified with five hundred forty-nine patients with dGIST: twenty-seven patients were treated with pancreatoduodenectomy and ninety-six with only local resection (segmental/wedge resections); in four hundred twenty-six patients it is not possible identify the type of treatment performed (pancreatoduodenectomy or segmental/wedge resections). Conclusions: dGISTs are a very rare subset of GISTs. They may be asymptomatic or may involve symptoms of upper GI bleeding and abdominal pain at presentation. Because of the misleading clinical presentation the differential diagnosis may be difficult. Tumours smaller than 2 cm have a low biological aggressiveness and can be followed annually by endoscopic ultrasound. The biggest ones should undergo radical surgical resection (R0). In dGIST there is no uniformly adopted surgical strategy because of the low incidence, lack of experience, and the complex anatomy of the duodenum. Therefore, individually tailored surgical approach is recommended. R0 resection with 1–2 cm clear margin is required. Lymph node dissection is not recommended due to the low incidence of lymphatic metastases. Tumor rupture should be avoided.